Measurement Accuracy of Heart Rate and Respiratory Rate during Graded Exercise and Sustained Exercise in the Heat Using the Zephyr BioHarnessTM - Kim, J.-H.; Roberge, R.; Powell, J. B.; Shafer, A. B.; Jon Williams, W. (International Journal of Sports Medicine, 2013)
The Zephyr BioHarnessTM was tested to determine the accuracy of heart rate (HR) and respiratory rate (RR) measurements during 2 exercise protocols in conjunction with either a laboratory metabolic cart (Vmax) or a previously validated portable metabolic system (K4b2). In one protocol, HR and RR were measured using the BioHarness and Vmax during a graded exercise up to V˙O2max (n=12). In another protocol, HR and RR were measured using the BH and K4b2 during sustained exercise (30% and 50% V˙O2max for 20 min each) in a hot environment (30 °C, 50% relative humidity) (n=6). During the graded exercise, HR but not RR, obtained from the BioHarness was higher compared to the Vmax at baseline and 30% V˙O2max (p<0.05), but showed no significant difference at other stages with high correlation coefficients for both HR (r=0.87–0.96) and RR (r=0.90–0.99 above 30% V˙O2max). During the exercise in the heat, there were no significant differences between the BioHarness and K4b2 system. Correlation coefficients between the methods were low for HR but moderately to highly correlated (0.49–0.99) for RR. In conclusion, the BioHarness is comparable to Vmax and K4b2 over a wide range of V˙O2 during graded exercise and sustained exercise in the heat.
Keywords: physiological monitoring; portable metabolic system; reliability